Climate Change Impacts on Polar Marine Ecosystems: Toward Robust Approaches for Managing Risks and Uncertainties - Ottersen, Geir; Constable, Andrew J.; Hollowed, Anne B.; Holsman, Kirstin K.; Melbourne-Thomas, Jess; Muelbert, Mônica M. C.; Skern-Mauritzen, Mette (Frontiers in Climate, 2022)
The Polar Regions chapter of the Intergovernmental Panel on Climate Change’s Special Report on the Ocean and Cryosphere in a Changing Climate (IPCC SROCC, 2019) provides a comprehensive assessment of climate change impacts on polar marine ecosystems and associated consequences for humans. It also includes identification of confidence for major findings based on agreement across studies and weight of evidence. Sources of uncertainty, from extent of available datasets, to resolution of projection models, to the complexity and understanding of underlying social-ecological linkages and dynamics, can influence confidence. Here we, marine ecosystem scientists all having experience as lead authors of IPCC reports, examine the development of primary sources of uncertainty for polar regions since SCROCC. Further synthesis of literature on polar marine ecosystems has been undertaken, especially within IPCC’s Sixth Assessment Report (AR6) Working Group II; for the Southern Ocean also the Marine Ecosystem Assessment for the Southern Ocean (MEASO). While knowledge gaps have been narrowed, we still find that polar region assessments reflect pronounced geographical skewness in data coverage and associated literature. There is also imbalance in scientific focus; especially research in Antarctica is dominated by physical oceanography and cryosphere science with highly fragmented approaches and only short-term funding to ecology. There are clear indications that uncertainty in the ability to project ecosystem responses to future climate change is being reduced by development of models and increased computer power allowing for better resolution in space and time. Lastly, we point forward – providing suggestions for future advances for IPCC assessments.